2014
DOI: 10.4103/0259-1162.143119
|View full text |Cite
|
Sign up to set email alerts
|

Role of Clonidine as adjuvant to intrathecal bupivacaine in patients undergoing lower abdominal surgery: A randomized control study

Abstract: Background:Neuraxial anesthesia greatly expands the anesthesiologist armamentarium, providing alternatives to general anesthesia, especially in the lower abdominal surgeries. Clonidine, an alpha-2 adrenergic agonist, has a variety of actions, including potentiation of effects of local anesthetics. This study was undertaken to assess the degree of sensory and motor block and postoperative analgesia provided by low dose (50 mcg) intrathecal clonidine admixed with bupivacaine.Aims:The aim of this study is to esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 21 publications
3
21
0
Order By: Relevance
“…Singh et al [152] studied Clonidine as an adjuvant to Bupivicaine in patients undergoing abdominal surgery. They showed that spinal anesthesia that contained Clonidine and Bupivicaine provided longer-lasting blockade of motor movement and sensation, as well as longer-term analgesia [152] compared to giving Bupivicaine alone.…”
Section: How Do Pharmacological Interventions Take Advantage Of Pamentioning
confidence: 99%
See 1 more Smart Citation
“…Singh et al [152] studied Clonidine as an adjuvant to Bupivicaine in patients undergoing abdominal surgery. They showed that spinal anesthesia that contained Clonidine and Bupivicaine provided longer-lasting blockade of motor movement and sensation, as well as longer-term analgesia [152] compared to giving Bupivicaine alone.…”
Section: How Do Pharmacological Interventions Take Advantage Of Pamentioning
confidence: 99%
“…Singh et al [152] studied Clonidine as an adjuvant to Bupivicaine in patients undergoing abdominal surgery. They showed that spinal anesthesia that contained Clonidine and Bupivicaine provided longer-lasting blockade of motor movement and sensation, as well as longer-term analgesia [152] compared to giving Bupivicaine alone. Similarly, Sen and Sen [153] found Clonidine to be an effective adjuvant to Bupivicaine and noted that patients who received Clonidine with Bupivicaine waited longer after surgery before requesting additional analgesia.…”
Section: How Do Pharmacological Interventions Take Advantage Of Pamentioning
confidence: 99%
“…16 Intrathecal clonidine is known for severe hypotension and bradycardia. 17 Compared to clonidine, dexmedetomidine produces optimal hypotension which decreases blood loss during major abdominal surgeries like hysterectomies. 18,19 One study conducted with different doses of intrathecal dexmedetomidine (5 µg, 10 µg, 15 µg and 20 µg) as an adjuvant to assess duration of sensory block, motor block and duration of pain relief concluded that 5 µg and 10 µg are optimal doses.…”
Section: -13mentioning
confidence: 99%
“…As a result, the dose response for clonidine by neuraxial administration is U shaped with peripheral vasoconstriction from circulating drug concentration at high doses opposing central sympatholysis. 19 In addition, clonidine directly inhibits sympathetic preganglionic neurons in the spinal cord. The degree of clonidine induced hypotension is related to the spinal level of injection.…”
Section: Sedationmentioning
confidence: 99%
“…The explanation for this could be that α2 agonist induce cellular modification in the ventral horn of spinal cord (motoneuron hyperpolarisation) and facilitate local anaesthetic action. 18,19 Clonidine may cause local vasoconstriction, thereby reducing vascular removal of local anaesthetics surrounding the neural structures. This may also partly explain increased duration of motor blockade associated with clonidine administration.…”
Section: Motor Characteristicsmentioning
confidence: 99%